Reverse diastolic flow of the fetal middle cerebral artery associated with placental chorangiomatosis and asymptomatic concealed placental abruption - David M. Sherer, MD; Olabisi Makanjoula, MD; Alessia Field, MD; Margarita Sokolovski, RDMS; Aleksandra Zigalo, RDMS; Sheila Hyppolite-Francis, RN; Mudar Dalloul, MD (Radiology Case Reports, 2023)
Reverse diastolic flow of the fetal middle cerebral artery is a rare, yet ominous finding which has been associated with adverse perinatal outcomes including: intracranial hemorrhage, growth restriction, fetal-maternal hemorrhage, severe anemia, hydrops, hepatic anomaly, subsequent stillbirth, and early neonatal death. We report a case in which following notation of a nonreassuring fetal heart rate at 32 weeks’ gestation, sonographic documentation of persistent reverse diastolic flow of the fetal middle cerebral artery was noted in association with sonographic findings of vascular placental dysmorphology and an asymptomatic concealed placental abruption. Subsequent fetal heart rate tracing consistent with uteroplacental insufficiency led to immediate Cesarean birth of an anemic yet nonacidotic, nonhypoxic neonate, who did well following management of respiratory distress syndrome and partial exchange transfusion. Placental abruption was confirmed at delivery. Histopathology of the placenta confirmed the presence of localized chorangiomatosis (“wandering” chorangioma). The association of reverse diastolic flow of the fetal middle cerebral artery, placental chorangiomatosis and placental abruption has not been reported previously. We conclude that in the presence of prenatal sonographic findings of placental dysmorphology and or placental abruption, insonation of the fetal middle cerebral artery should be performed to assess the possibility of increased peak systolic velocity and possible reverse diastolic flow, both associated with fetal anemia and increased likelihood of an adverse perinatal outcome.